Perspective Financial Ratios in Assessing the Performance of Stock on Textile Sector Firm Listed on the Indonesia Stock Exchange - Yunike Berry (Jurnal Manajemen Universitas Bung Hatta, 2023)
Observing the rise in investors in the Indonesian stock exchange, particularly during the Covid 19 pandemic, the author is interested in research on fundamental analysis in assessing stock prices on the Indonesian stock exchange, especially firms in the textile and apparel sectors. This research investigates how financial ratios affect stock values from 2018 to 2020. A total of 16 firms serve as research samples. This research used panel data and was analyzed by a regression test of panel. From the test results, it was found that variables price book value, price earning ratio, quick ratio, return on total assets and total asset turnover has effect on stock price while there was no effect of debt Ratio and rurrent ratio on stock price in garment and textiles sector for 2018-2020.